Pharmacological Treatments for Cocaine Craving: What Is the Way Forward? A Systematic Review - Dângela Layne Silva Lassi; André Malbergier; André Brooking Negrão; Lígia Florio; João P. De Aquino; João Maurício Castaldelli-Maia (Brain Sciences, 2022)
Background: cocaine craving is a core feature of cocaine use disorder and remains a critical challenge for abstinence and relapse prevention. This review summarizes the anti-craving efficacy of pharmacotherapies tested for cocaine use disorder, in the context of randomized-controlled clinical trials. Objectives: we assessed the databases of the U.S. National Library of Medicine, Google Scholar, and PsycINFO, without date restrictions up to August 2022, to identify relevant studies. Study eligibility criteria, participants, and interventions: we included double-blinded randomized-controlled trials investigating pharmacotherapies for cocaine craving and/or cocaine use disorder whose outcomes included cocaine craving. Study appraisal and synthesis methods: Two authors screened studies’ titles and abstracts for inclusion, and both read all the included studies. We systematically gathered information on the following aspects of each study: title; author(s); year of publication; sample size; mean age; sample characteristics; study set-ting; whether participants were treatment-seeking; study design; craving measures; study interventions; drop-out rates; and other relevant outcomes. Results: Overall, we appraised 130 clinical trials, including 8137 participants. We further considered the drugs from the studies that scored equal to or greater than six points in the quality assessment. There was a correlation between craving and cocaine use outcomes (self-reports, timeline follow-back or urinary benzoylecgonine) in the vast majority of studies. In the short-term treatment, acute phenylalanine-tyrosine depletion, clonidine, fenfluramine, meta-chlorophenylpiperazine (m-CPP) and mecamylamine presented promising effects. In the long term, amphetamine, biperiden, carbamazepine, lisdexamfetamine, lorcaserin, methamphetamine, mirtazapine, pioglitazone, progesterone, guanfacine, levodopa, nefazodone presented promising anti-craving effects. Unfortunately, the highly tested medications were not successful in most of the trials, as follows: propranolol in the short term; amantadine, aripiprazole, bromocriptine, citicoline, ketamine, modafinil, olanzapine, topiramate in the long term. The remaining 52 medications had no positive anti-craving outcomes. Limitations: Our review was limited by high heterogeneity of craving assessments across the studies and by a great range of pharmacotherapies. Further, the majority of the studies considered abstinence and retention in treatment as the main outcomes, whereas craving was a secondary outcome and some of the studies evaluated patients with cocaine use disorder with comorbidities such as opioid or alcohol use disorder, schizophrenia, bipolar disorder or attention deficit hyperactivity. Lastly, most of the studies also included non-pharmacological treatments, such as counseling or psychotherapy. Conclusions: There is a direct association between craving and cocaine use, underscoring craving as an important treatment target for promoting abstinence among persons with cocaine use disorder. Clonidine, fenfluramine and m-CPP showed to be promising medications for cocaine craving in the short-term treatment, and amphetamine, biperiden, carbamazepine, lisdexamfetamine, lorcaserin, methamphetamine, mirtazapine, pioglitazone, progesterone, guanfacine, levodopa, nefazodone in the long-term treatment.